The Influence of Entrepreneurship Class Program on Career Maturity of Vocational School Students - Jati, Revina Sedyaning; Wahyuni, Fitri (Universitas Negeri Malang, 2024)
Career maturity refers to the process by which an individual develops a deep understanding of oneself, career interests, values, and goals they wish to achieve in their career. The lack of career maturity in students prompts schools to facilitate them by organizing entrepreneur classes. Therefore, the aim of this research is to investigate the influence of entrepreneur class programs on the career maturity of vocational high school students. The methodology employed in this research is qualitative descriptive design. The subjects of the study consist of three students from Muhammadiyah 7 Gondanglegi Vocational High School enrolled in the entrepreneur class, three graduate students from the entrepreneur class, and a teacher who serves as the head of the entrepreneur class committee. Data collection techniques include interviews, observations, and documentation using interview guidelines, observation guides, and documentary studies as instruments. The data analysis technique used is triangulation analysis of sources. The findings of the research indicate that the entrepreneur class program indeed has a significant positive influence on the career maturity of vocational high school students.